Student videos as a tool for elementary teacher development in teaching engineering: What do teachers notice?. - McCormick, Mary E.; Wendell, Kristen.; O'Connell, Brian Patrick. (Tufts University. Tisch Library., 2017)
The Next Generation Science Standards call for all K-12 students to participate in practices of engineering and to consider core disciplinary ideas of engineering design. This inclusion of engineering in the NGSS heightens the engineering education community's need to develop effective supports for K-12 teachers learning to teach engineering. In our work, we explore approaches to supporting elementary school teachers as they learn to facilitate integrated engineering and literacy experiences in their classrooms. We are interested in effective ways to help teachers learn to conduct these engineering activities so that their students take agency not just in building prototypes based on children's books but also in the important engineering practices of problem scoping, conceptual planning, and realizing and testing design ideas. Our goal is to support in-service elementary teachers in learning to identify and respond productively to the beginnings of engineering in their students. In this qualitative research study, we investigated student video as a tool for elementary teacher development in engineering. We used clinical interviews to answer the research question, how do elementary teachers identify and respond to children's engineering in a video episode viewed before formal professional development? Our purpose was to discern teachers' baseline analysis of student engineering so that we could design professional development programs better tailored to help teachers improve their engineering pedagogy. Five teachers participated in the clinical interviews. All five were new to the integrated engineering and literacy approach. In the interviews, the teachers described how they facilitate small group projects in their own classrooms. They then watched an episode of three third-grade students solving an engineering problem based on a non-fiction text about the colonial era in America. Finally, they shared what they noticed about the students' engineering work in the video episode and how they might respond to the students in the episode. We analyzed the interview transcripts using a systematic, iterative process drawing from methods of grounded theory and constant comparative analysis. We (the three authors)comprehensively reviewed all transcripts and generated emergent codes for the areas where teachers focused their attention and the ways that teachers were framing the video analysis task. We then conducted line-by-line coding to assign each utterance a code for focus of attention and a code for task framing. We iterated on code definitions and assignments until reaching consensus on a set of themes that described the different ways the teachers approached the task of identifying and responding to student engineering work. The three most salient stances taken by teachers were empathizer with student perspective, holder of engineering knowledge, and authoritative instructor and assessor. Our analysis suggests that these three stances were not mutually exclusive but that teachers shifted among the stances depending on the focus of their attention and the support of the interviewer. In this paper, we present the full findings from our analysis. We discuss the implications of these results for designing professional development that supports teachers' productive identification of and response to the beginnings of engineering in students' work.